Neermathalam Pootha Kalam - Madhavikkutti (DC Books, 1993)
A book which bears the flowering memories of life. Neermathalam Pootha Kalam is a collection of cherished memories which gives a nostalgic effect to the readers. It is a memoir by Madhavikkutty.